Thermoeconomic Analyses of Heat Pumps - Oztekin, Erman Kadir; Gur, Mehmet Murat; Karaali, Rabi (International Journal of Computational and Experimental Science and Engineering, 2025)
Recently, the rapid development of technology and the increase in energy costs and needs have made reducing the costs and efficient use of energy and exergy important. The thermoeconomic analysis method, which is the best cost analysis method of energy and exergy, gives the ways to reduce costs and increase efficiency that can be applied a facility. It has been found that the most suitable thermoeconomic solution for winter heating and summer cooling of a facility is a vertical underground source heat pump and the most high-performance working fluid that should be used is R32. If the heating is done with a ground source heat pump instead of electrical energy, 4.25 kW of heating energy will be obtained for each kW of electrical energy given for heating, since the costs are COPIP 4.25. Here the earnings increase by around 325%. In other words, heating costs decrease by around 77.5 percent, that is, from one hundred liras to 22.5 liras.